2017
DOI: 10.1109/jbhi.2016.2621887
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Atrial Fibrillation Based on Time–Frequency Analysis of Seismocardiograms

Abstract: In this paper, a novel method to detect atrial fibrillation (AFib) from a seismocardiogram (SCG) is presented. The proposed method is based on linear classification of the spectral entropy and a heart rate variability index computed from the SCG. The performance of the developed algorithm is demonstrated on data gathered from 13 patients in clinical setting. After motion artifact removal, in total 119 min of AFib data and 126 min of sinus rhythm data were considered for automated AFib detection. No other arrhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 35 publications
0
64
0
Order By: Relevance
“…In addition to human studies on healthy populations, there were several studies that focused on the application of SCG in patients with cardiovascular disease. SCG signals were used for diagnosis and monitoring of different clinical conditions such as atrial fibrillation [47,48,68,70], atrial flutter [55], heart valve disease [37,44,80], coronary artery disease and ischemia [9,10,48], myocardial infarction [126], heart failure [75,78,82,100,119], structural heart disease [80], and heart stress testing [58].…”
Section: Scg In Patients With Cardiac Conditionsmentioning
confidence: 99%
“…In addition to human studies on healthy populations, there were several studies that focused on the application of SCG in patients with cardiovascular disease. SCG signals were used for diagnosis and monitoring of different clinical conditions such as atrial fibrillation [47,48,68,70], atrial flutter [55], heart valve disease [37,44,80], coronary artery disease and ischemia [9,10,48], myocardial infarction [126], heart failure [75,78,82,100,119], structural heart disease [80], and heart stress testing [58].…”
Section: Scg In Patients With Cardiac Conditionsmentioning
confidence: 99%
“…In [ 11 ], the heart condition is estimated from the learned morphology of seismocardiography. In [ 24 ], SCG based automated detection of atrial fibrillation is demonstrated. In [ 25 ], a comparative study on pulse transit time measurement using seismocardiography, photoplethysmography and acoustic recordings is carried out.…”
Section: Related Workmentioning
confidence: 99%
“…To the best of our knowledge, the state-of-art recent studies [ 6 , 8 , 23 ] exclusively focus on separate or combined annotation of ECG and SCG or focus on the annotation based disease-specific cardiac function monitoring [ 9 , 24 ]. However, mere annotation of morphologies may not provide the powerful insight unless the comprehensive theoretical analysis is explored.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, such approach enables to involve the various recording methods which can provide signals in which the heartbeats can be detected. Beside electrocardiogram, such signals include photoplethysmogram [22][23][24] or seismocardiogram [25]. Using a photoelectric sensor is attractive in case of home telecare as long-term recording should be accomplished by instrumentations being minimally troublesome and inconvenient to the patient [26,27].…”
Section: Introductionmentioning
confidence: 99%